Spatial regularity in suicides and alcohol psychoses in Belarus - Razvodovsky, Yury E.; Kandrychyn, Sergey V. (Acta medica Lituanica, 2014)
Objective. Epidemiological evidence suggests that rates of suicide mortality vary noticeably between the regions in Belarus with the regular spatial pattern in suicide distribution. The present study considers the effect of regional alcohol consumption as a factor responsible for regional variations in suicide rates. Methods. The cross-sectional time series analysis of suicide and alcohol psychoses (as a proxy for alcohol consumption) rates by the regions of Belarus between 1990 and 2010 was made. Results. In general, the regional variations of suicide and alcohol psychoses incidence rates have a similar spatial regularity, meaning that the regions with a high suicide rate also have a high alcohol psychoses incidence rate. Conclusions. The findings on spatial relationship between suicide and alcohol psychoses incidence rates seem to support the hypothesis that considers the regional pattern of alcohol consumption as a factor responsible for suicide rate regional variations.
Keywords: suicide; alcohol psychoses; spatial regularity; Belarus